HEALTH OF ISLAMIC COMMERCIAL BANKS IN INDONESIA: CAMEL AND RGEC METHODS - Fitriyah, Fitriyah; Abdillah, Mukhsin (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aims to evaluate the health of Islamic Commercial Banks in Indonesia during the period 2021-2023 using the CAMEL and RGEC methods. The stability and health of banks are crucial factors in maintaining customer trust and the continued operation of Islamic banking in Indonesia. The research employs a qualitative approach with analysis based on the CAMEL (Capital Adequacy, Asset Quality, Management, Earnings, Liquidity) and RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) methods. The data analyzed are derived from the annual financial reports of Islamic Commercial Banks during the period 2021-2023, with data collection techniques conducted through documentation studies. The results of the study indicate that Bank Mega Syariah and Bank Central Asia Syariah received a "Healthy" rating based on the CAMEL method. Meanwhile, Bank Aceh, BTPN Syariah, Bank Riau Kepri Syariah, Bank Syariah Indonesia, Bank NTB Syariah, Bank Victoria Syariah, Bank Jabar Banten Syariah, and Bank Muamalat Syariah were rated "Fairly Healthy." The differences in these assessments are primarily due to variations in the Return on Assets (ROA) and Operating Costs to Operating Income (BOPO) ratios. In contrast, the RGEC method showed that Bank Riau Kepri Syariah, Bank Aceh, BTPN Syariah, and Bank Syariah Indonesia received a "Very Healthy" rating, while Bank Mega Syariah, Bank Central Asia Syariah, Bank NTB Syariah, Bank Victoria Syariah, and Bank Jabar Banten Syariah were rated "Healthy." Bank Muamalat Indonesia was rated "Less Healthy" due to variations in ROA, Return on Equity (ROE), Net Operating Margin (NOM), and BOPO ratios across the banks.